APPLICATION OF EXPERIMENTAL SIMULATION SOFTWARE TO IMPROVE STUDENT'S ENGAGEMENT IN CHEMISTRY PRACTICAL EXPERIMENTS - Ekwe, Bertrand Ezenwa (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2022)
The increasing development in technological innovations has offered opportunities that foster teaching and learning at every level of the education system. Computer simulation tools have increased students' motivation, interest, and engagement in science education. The present study examined ChemLab simulation software as a tool that could influence students' engagement in chemistry laboratory experiments in secondary school. Two hundred and nine senior secondary school students enrolled in the science classes participated in the study. The result established a statistically significant effect of ChemLab simulation software on the respondent's intention to engage in chemistry lab experiments at F (1,207), 4.60 P< .05 with adjusted R2 indicating that ChemLab simulation software contributed about 9.11% of the variance in student's intention to engage in a chemistry lab experiment. The finding has implications for developing chemistry laboratory experiments in secondary schools.